(untitled) (Zaporizhzhia Historical Review, 2021)
Inspection of Pereyaslav regiment from 1750 is characterized. Individual, service and economic sample data of “neuradova starshyna” of regiment are given in the article. Key words: inspection, regiment, “sotna”, cossack, “neuradova starshyna”, “bunchukovyi” comrade, “viyskovyi” comrade, “znachkovyi” comrade.